2016
DOI: 10.1002/ana.24647
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities are a core feature of Alzheimer's disease: Evidence from the dominantly inherited Alzheimer network

Abstract: Objective White matter hyperintensities(WMH) are areas of increased signal on magnetic resonance imaging(MRI) scans that most commonly reflect small vessel cerebrovascular disease. Increased WMH volume is associated with risk and progression of Alzheimer’s disease(AD). These observations are typically interpreted as evidence that vascular abnormalities play an additive, independent role contributing to symptom presentation, but not core features of AD. We examined the severity and distribution of WMH in presym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
452
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(490 citation statements)
references
References 52 publications
34
452
2
2
Order By: Relevance
“…Increased HR can be a sign of cardiac problems, predicts incident cardiovascular events (50), and is not typically affected by aging. Therefore, some of the subjects in the sample may have experienced deterioration in overall cardiovascular health over time, potentially leading to cerebrovascular changes, a proposed core feature of AD (51). Increases in resting HR may also be capturing changes in HR variability (52), which may be sensitive to AD detection and severity (11).…”
Section: Discussionmentioning
confidence: 99%
“…Increased HR can be a sign of cardiac problems, predicts incident cardiovascular events (50), and is not typically affected by aging. Therefore, some of the subjects in the sample may have experienced deterioration in overall cardiovascular health over time, potentially leading to cerebrovascular changes, a proposed core feature of AD (51). Increases in resting HR may also be capturing changes in HR variability (52), which may be sensitive to AD detection and severity (11).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the hypoperfusion actually damages the brain, even in preclinical or early disease, is well demonstrated on imaging of cerebral white matter in people with mutations that cause autosomal dominant forms of AD. A recent study showed that people with such mutations had a greater volume of white matter hyperintensities (WMH) several years before clinical disease, indicating that the hypoperfusion was severe enough to cause tissue damage (67). The increase in WMH was most pronounced in the parietal and occipital lobes; as noted above, this corresponds approximately to the distribution of early amyloid accumulation and reduced perfusion in the overlying cerebral cortex.…”
Section: Reduced Demand or Reduced Supply?mentioning
confidence: 91%
“…The authors found that amyloid burden, as assessed by measuring Aβ42 level in the CSF, was an independent predictor of total WMH volume. Lee and colleagues (67) found some correlation between WMH and the presence of microbleeds, suggesting a contribution from cerebral amyloid angiopathy. However, the increase in WMH remained significant after controlling for presence of microbleeds, which were calculated to account for 21% of the association between AD mutation status and WMH.…”
Section: Reduced Demand or Reduced Supply?mentioning
confidence: 98%
“…Cerebral blood flow (CBF) declines before cognitive decline or brain atrophy [1,8] and is associated with biochemical and MRI evidence of tissue damage [4,9]. Vessel wall abnormalities such as cerebral amyloid angiopathy (CAA) and arteriolosclerosis, may play a part in the hypoperfusion but its timing and distribution suggest that other factors are more important contributors.…”
Section: Introductionmentioning
confidence: 99%